2021
DOI: 10.1088/1748-9326/abe14b
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the combined impacts of weeds and climate change on crops

Abstract: Crops worldwide are simultaneously affected by weeds, which reduce yield, and by climate change, which can negatively or positively affect both crop and weed species. While the individual effects of environmental change and of weeds on crop yield have been assessed, the combined effects have not been broadly characterized. To explore the simultaneous impacts of weeds with changes in climate-related environmental conditions on future food production, we conducted a meta-analysis of 171 observations measuring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 53 publications
2
23
0
1
Order By: Relevance
“…Weed management will also experience new challenges. For instance, while glyphosate has been projected to lose its efficacy on weeds as CO 2 levels rise, there are also predictions that increased atmospheric CO 2 concentrations will have a positive impact on several weed species, which may contribute to increased risk of crop loss due to weed pressure (Vilá et al., 2021). As a result, both herbicide use and costs are expected to increase as CO 2 levels rise (Koleva & Schneider, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Weed management will also experience new challenges. For instance, while glyphosate has been projected to lose its efficacy on weeds as CO 2 levels rise, there are also predictions that increased atmospheric CO 2 concentrations will have a positive impact on several weed species, which may contribute to increased risk of crop loss due to weed pressure (Vilá et al., 2021). As a result, both herbicide use and costs are expected to increase as CO 2 levels rise (Koleva & Schneider, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…They reported that climate change favors the expansion, growth and multiplication of wheat pests. Furthermore, climate change opens new geographic windows for weed infestations (Mao et al, 2021;Vilà et al, 2021), insect biodiversity (Raven & Wagner, 2021) and disease outbreaks (Chaloner et al, 2021) across Fig. 6 Interactive effect of elevated CO 2 , temperature, and drought on soil organic carbon the globe.…”
Section: Overview Of Responses To Biotic Stressesmentioning
confidence: 99%
“…Generally, weeds or plant species show three kinds of reactions to climate change i.e. (i) migration; (ii) acclimation and (iii) adaptation (Vilà et al, 2021). In the future, we will have to adopt sustainable weed management options to minimize the impact of weeds on cropping systems.…”
Section: Overview Of Responses To Biotic Stressesmentioning
confidence: 99%
“…While changes in land‐use type and intensity have substantially affected the biota of arable habitats (Storkey et al, 2012) there is growing evidence that species are increasingly responding to climate change (Parmesan & Yohe, 2003; Chen et al, 2011). As climate change will continue in the coming decades (IPCC, 2022), the resulting impacts on arable habitats and their biota will become more pronounced (Ziska, 2016; Vilá et al, 2021). In addition, arable habitats in Central Europe show high levels of invasion by alien plant species introduced both a long time ago (i.e.…”
Section: Introductionmentioning
confidence: 99%